Implementing 6 steps of Imam Ghazali evaluation process: the case of Oshien2u Sdn. Bhd. company - Ahmad Razimi, Mohd Shahril; Romle, Abd Rahim; Mufti, Mohamad Syubhana (IDOSI Publications, 2017)
Islam as the religion of life thought community always evaluating on self-activities either in good quality activities or not.In Human Resources, evaluating performance is the importance step on ensure productivity of company achieving the goals of company.Imam Ghazali has identified 6 stepson process to control and evaluating performance. Oshien2u Sdn. Bhd. as one of big company in Malaysia will be the case study on this paper. This paper will explore either Oshien2u company following the 6 steps of Imam Ghazali Theory in development and evaluating on staff performance and how Oshien2ucompany applied this theory in practice.